2019
DOI: 10.1111/edt.12521
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of 79 traumatically intruded permanent teeth in Chinese children and adolescents: A retrospective study

Abstract: Background/Aim Data on the clinical outcomes of traumatically intruded, young, permanent teeth in Chinese children and adolescents are absent. The aim of this study was to examine the probability of spontaneous re‐eruption of injured teeth, to investigate the incidence of pulp necrosis with infection of the root canal system and replacement root resorption and to analyse possible factors related to healing complications after injury. Materials and Methods Clinical data from 6‐ to 18‐year‐old patients who susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 14 publications
1
25
1
Order By: Relevance
“…Pulp necrosis is the most commonly found complication following extrusion, 16 intrusion, 2 and lateral luxation 17 . Mature incisors with a closed apical foramen have a higher risk of pulp necrosis, 18, 19 with rates of up to 100% for intrusion 1 . If pulp necrosis is diagnosed or seems inevitable, the indication for endodontic treatment is given 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Pulp necrosis is the most commonly found complication following extrusion, 16 intrusion, 2 and lateral luxation 17 . Mature incisors with a closed apical foramen have a higher risk of pulp necrosis, 18, 19 with rates of up to 100% for intrusion 1 . If pulp necrosis is diagnosed or seems inevitable, the indication for endodontic treatment is given 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that OE may lead to better results in 90.3% of the teeth 8 . However, it is important to note that extrusion may also result in calcific metamorphosis, which is caused by the deposition of tertiary dentin on the dentinal walls, 17 and be related to more cases of replacement root resorption 18 . Following orthodontic treatment, there is an increased risk for root resorption even in intact teeth 19,20 that may be induced by the pressure in the periodontal ligament 21 .…”
Section: Introductionmentioning
confidence: 99%
“…8 However, it is important to note that extrusion may also result in calcific metamorphosis, which is caused by the deposition of tertiary dentin on the dentinal walls, 17 and be related to more cases of replacement root resorption. 18 Following orthodontic treatment, there is an increased risk for root resorption even in intact teeth 19,20 that may be induced by the pressure in the periodontal ligament. 21 According to a recently published meta-analysis, there is a higher incidence of root resorption in vital teeth as compared to roottreated teeth.…”
Section: Introductionmentioning
confidence: 99%
“…1,26 Orthodontic repositioning of traumatically intruded teeth might result in clinical complications such as root resorption and pulp necrosis. 31 In this issue, a retrospective study of the effects of extrusion of traumatically intruded teeth was conducted. Shalish et al compared adverse effects after orthodontic extrusion of traumatically intruded teeth to the treatment of non-traumatized teeth.…”
mentioning
confidence: 99%
“…The current IADT guidelines recommend spontaneous eruption, orthodontic extrusion, and surgical repositioning as three treatment options for repositioning intruded teeth 1,26 . Orthodontic repositioning of traumatically intruded teeth might result in clinical complications such as root resorption and pulp necrosis 31 . In this issue, a retrospective study of the effects of extrusion of traumatically intruded teeth was conducted.…”
mentioning
confidence: 99%